2019
DOI: 10.1111/chd.12708
|View full text |Cite
|
Sign up to set email alerts
|

PDA: To treat or not to treat

Abstract: Management of patent ductus arteriosus in extremely preterm infants remains a topic of debate. Treatment to produce ductal closure was widely practiced until the past decade, despite lack of evidence that it decreases morbidities or mortality. Meta‐analyses of trials using nonsteroidal anti‐inflammatory drugs have shown effectiveness in accelerating ductal closure, but no reduction in neonatal morbidities, regardless of agent used, indication, timing, gestational age, or route of administration. Surgical ligat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…Evidence showed that while treatment was effective in achieving ductal closure, only a single study showed improvement in other outcomes such as pulmonary hemorrhage, BPD, NEC, or death. Correlations between PDA and IVH were and did not support the hypothesis that closure of the ductus improves neurological outcomes [16][17][18][19][20][21][22]. It was concluded that the association of comorbidities with PDA might arise from prematurity itself rather than through prolonged patency of the ductus.…”
Section: Controversy and Practice Variationmentioning
confidence: 91%
See 3 more Smart Citations
“…Evidence showed that while treatment was effective in achieving ductal closure, only a single study showed improvement in other outcomes such as pulmonary hemorrhage, BPD, NEC, or death. Correlations between PDA and IVH were and did not support the hypothesis that closure of the ductus improves neurological outcomes [16][17][18][19][20][21][22]. It was concluded that the association of comorbidities with PDA might arise from prematurity itself rather than through prolonged patency of the ductus.…”
Section: Controversy and Practice Variationmentioning
confidence: 91%
“…Although the pathogenesis of BPD is complex, associations between prolonged exposure to a moderate-to-large PDA and BPD have been documented [18,19]. Additional research further established the association of PDA with systemic complications such as NEC, renal impairment, IVH, periventricular leukomalacia (PVL), cerebral palsy, and death [20][21][22].…”
Section: Consequences Of Pda In Elbw Infantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment was withheld if there was identification of gastrointestinal bleeding or oliguria (urine output of less than 1 mL/kg/hour) according to the protocol for PDA management in our NICU. The decision was made by the neonatologists to transfer the ELBWI for surgical ligation if more than two courses of oral ibuprofen were given and the PDA was still significant [11].…”
Section: Methodsmentioning
confidence: 99%